Destabilizing the center, disrupting the flow: Culture, mobility, and learning in the construction of female identity - Barbara Sparks (Adult Education Research Conference, 2006)
This study looked at how women experience the destabilizing effects of change when the flow of their lives is disrupted, either intentionally or unintentionally? The life histories of four women reveal themes of opportunities for re-forming identities, cultural aspects of the self which create meaning for the self and one’s place in the world, and historical factors and positioning within temporal parameters.
Keywords: Women in adult education; critical social geography; life history